Phosphoproteome analysis reveals chitosan-induced resistance to osmotic stress in rice (Oryza sativa L.) seedlings. Issue 1 (31st December 2022) - Pongprayoon, Wasinee; Maksup, Sarunyaporn; Phaonakrop, Narumon; Jaresitthikunchai, Junthima; Uawisetwathana, Umaporn; Panya, Atikorn; Roytrakul, Sittiruk
ABSTRACT: This study sought to identify the mechanism underlying the response to chitosan at the posttranslational level. Khao Dawk Mali 105 seeds were soaked in 40 mg l −1 of chitosan, and leaves of 2- and 4-week-old seedlings were sprayed with chitosan before starting osmotic stress conditions. Chitosan induced resistance to osmotic stress by enhancing shoot fresh and dry weights and maintained increased photosynthetic pigments. Leaf phosphoproteomes were examined using gel-free LC-MS/MS. Of the 60 phosphoproteins showed a significant difference in protein expressions under osmotically-stressed plants treated with chitosan. More than 40% of the phosphoproteins involved in signaling pathways, including OsCML12 calmodulin-related calcium sensor protein, ubiquitin carboxyl-terminal hydrolase 15, U-box domain-containing protein 45, HEAT repeat family protein, BRCA1 C terminus domain-containing protein, pectinesterase, protein kinase domain-containing protein, and receptor-like protein kinase. Chitosan enhanced rice seedling growth and drought resistance via multiple complex networks, including metabolism, transport, transcription, and signaling under osmotic stress.